Universal polymerase chain reaction screening for severe acute respiratory syndrome coronavirus 2 infections among patients who visited the Department of Otolaryngology-Head and Neck Surgery, Tohoku University Hospital - Kakuta, Risako; Kanamori, Hajime; Tokuda, Koichi; Kitaya, Shiori; Katori, Yukio (Journal of Immunology, Allergy and Infection in Otorhinolaryngology, 2022)
Introduction: The coronavirus disease 2019 became a global pandemic in the spring of 2020 and remains a major threat to public health worldwide, including in Japan. In otolaryngology-head and neck surgery, aerosol-generating procedures are performed; thus, caution was alerted from an early stage. Since April 2020, our department has been conducting universal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction (PCR) screening tests before surgery or admission. Here, we assessed the SARS-CoV-2-PCR screening tests in otolaryngology-head and neck surgery.Methods: We investigated cases of SARS-CoV-2-PCR screening tests that were performed at the Department of Otorhinolaryngology-Head and Neck Surgery, Tohoku University Hospital, from April 2020 to October 2021.Results: The total number of screening test subjects in our department was 1,123, and the purpose of the test was (1) surgery in 807 cases (71.9%) and (2) hospitalization other than surgery in 298 cases (26.5%). (3) Fifteen cases (1.3%) were judged to be necessary by the physician on the questionnaire and three cases (0.3%) were others. Some patients had upper respiratory tract symptoms or fever, but the screening tests in our department showed negative results, including these cases.Discussion: Although all screening test cases showed negative results in our study, there are reports of asymptomatic positive cases in Japan and other countries. Screening tests are useful to prevent secondary infections and outbreaks of in-hospital clusters, and it is necessary to further consider sustainable test formats for the early detection of asymptomatic individuals.